2012
DOI: 10.3109/01913123.2011.620220
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in Cerebral Capillary Pericytes in Aged Notch3 Mutant Transgenic Mice

Abstract: Pericytes, the specialized vascular smooth muscle cells (VSMCs), play an important role in supporting and maintaining the structure of capillaries. Pericytes show biochemical and physiologic features similar to VSMC, usually containing smooth muscle actin fibers and rich endoplasm reticulum. Studies have indicated that degeneration of VSMCs due to Notch3 mutations is the cause of cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL). However, it remains unclear wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Since Notch3 has a critical role in the recruitment of pericytes as well as VSMC proliferation [24,25], we first examined the role of Notch3 deficiency on pericyte coverage and VSMC in vivo using the mouse model of retinal angiogenesis. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since Notch3 has a critical role in the recruitment of pericytes as well as VSMC proliferation [24,25], we first examined the role of Notch3 deficiency on pericyte coverage and VSMC in vivo using the mouse model of retinal angiogenesis. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings reconfirm previous observations by other groups that used electron microscopy to detect ultrastructural changes in pericytes in postmortem tissue samples from CADASIL patients. 17,18 To rule out the possibility that overexpressing mutant Notch3 merely caused a downregulation of PDGFRb in well-preserved pericyte processes, we used a second pericyte-specific marker, desmin, confirming that pericyte coverage of the microvasculature decreases with age. In contrast to previous reports using PDGFRb-knockout mice, 9,13 the age-dependent loss of microvascular pericyte coverage in our CADASIL mouse model was not accompanied by a decrease in capillary density or vascular diameter.…”
Section: Discussionmentioning
confidence: 99%
“…The Notch3 receptor is also expressed in capillary pericytes, and recent electron microscopy studies found altered pericyte morphology in CADASIL mice. 17,18 However, the functional relevance of these findings is unclear, and the role of pericytes in the initiation and progression of CADASIL is currently unknown. Therefore, the aim of this study was to examine whether pericytes play a role in the pathogenesis of CADASIL.…”
mentioning
confidence: 99%
“…These data indicate an abnormal BBB in Notch3 mutated animals. Notch3 mutant pericytes in mice show an increase in the number of abnormal pericytes in vivo , and morphologically, these cells display severe cellular injury(Gu et al, 2012). Recent evidence demonstrate that newborn Notch3-deficient mice have greatly reduced expression of PDGF-Rβ on pericytes, and PDGF-Rβ expression was amplified with Notch ligand activation(Jin et al, 2008).…”
Section: Pericyte-endothelial Cell Interactionmentioning
confidence: 99%